Penerapan Sistem Accurate pada Arus Kas di CV. Anugrah Unika Mekanik Sidoarjo Tahun 2017-2018 - Dwi Setyo, Ananta (Akuntansi: Jurnal Akuntansi Integratif, 2019)
This journal is the result of qualitative research that aims to answer questions about how the Implementation of Accurate Systems in Cash Flow and the Implications of the Application of the Accurate System to Cash Flow in CV. Grace of Sidoarjo Mechanics for 2017- 2018. The method used in this study is qualitative with a type of case study research. The researcher collected data through interviews with the finance department and documentation, the data analysis technique used in this study was from the results of interviews and documentation, then the data obtained was processed and analyzed after it was concluded and interpreted. The results of this study indicate that: The cash flow accounting information system applied to the CV. Anugrah Unika Mekanik uses a manual system. Cash flow in not using a computerized system and manual recording and reporting causes many documents to be lost, incomplete, and not neatly arranged. The use of Accurate Accounting Software can overcome the shortcomings mentioned and increase work efficiency and effectiveness.